Connection between the vibrational dynamics and the cross‐linking properties in cyclodextrins‐based polymers1. (31st March 2013) - Crupi, Vincenza; Fontana, Aldo; Giarola, Marco; Majolino, Domenico; Mariotto, Gino; Mele, Andrea; Melone, Lucio; Punta, Carlo; Rossi, Barbara; Trotta, Francesco; Venuti, Valentina
Abstract : The vibrational dynamics of a new class of cross‐linked polymers obtained from both native and modified cyclodextrin, referred to as cyclodextrin nanosponges, is here investigated. The main purpose is to spot the structure of these materials at molecular level unlikely to be characterized by diffraction methods due to the low or null degree of crystallinity. The analysis of the spectral features of the vibrational bands observed between 1650 and 1800 cm −1 in both Raman and infrared spectra, and assigned to the carbonyl stretching modes of the polymeric network, is performed by using band deconvolution procedures. At the same time, a detailed inspection of the low‐wavenumber vibrational dynamics of these polymers is carried out, focusing on the modifications occurring on the so‐called boson peak. The simultaneous analysis of different wavenumber ranges in Raman and infrared spectra of cyclodextrin nanosponges allows us to develop a reliable strategy for exploring both the cross‐linking degree and the elastic properties of these innovative materials. The overall results give a complete characterization of the structural and dynamical properties of the system, in turn strictly connected to the entrapment/transport ability of these polymeric matrices. Copyright © 2013 John Wiley & Sons, Ltd. Abstract : The vibrational dynamics of a new class of cyclodextrin‐based cross‐linked polymers is here investigated. The simultaneous analysis of intermolecular vibrational bands and of the so‐called boson peak allowed us to deeply explore the cross‐linking degree and the elastic properties of these innovative materials.